2010
DOI: 10.1016/j.toxlet.2010.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 knockout enhances astrocyte toxicity induced by 1-methyl-4-phenylpyridinium ion and lipopolysaccharide via increasing the expression of cytochrome P4502E1

Abstract: The role of aquaporin-4 (AQP4) in the regulation of astrocytes function has been widely investigated. However, there is little information about its contribution to the drug metabolism enzymes such as Cytochrome P4502E1. In the present study, we investigated whether AQP4 is involved in the process of the cell damage caused by MPP + and LPS through regulating the expression of CYP2E1 in astrocytes. Compared to the wild-type, in primary astrocytes, AQP4 knockout increased the cell damage and the reactive oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
6
16
0
Order By: Relevance
“…For example, the early induction of AQP4 by a low dose of thrombin contributes to limitation of the ischemic infarction and formation of edema in mice [48] , and acute vascular disruption is associated with AQP4 loss after transient MCAO in rats [49] . This protective role is also reported in spinal cord compression injury [50] , subarachnoid hemorrhage [51] , intracerebral hemorrhage [52] and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity [53,54] . These findings demonstrate that AQP4 in astrocytes exerts a beneficial action in pathological conditions.…”
Section: Discussionsupporting
confidence: 56%
“…For example, the early induction of AQP4 by a low dose of thrombin contributes to limitation of the ischemic infarction and formation of edema in mice [48] , and acute vascular disruption is associated with AQP4 loss after transient MCAO in rats [49] . This protective role is also reported in spinal cord compression injury [50] , subarachnoid hemorrhage [51] , intracerebral hemorrhage [52] and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity [53,54] . These findings demonstrate that AQP4 in astrocytes exerts a beneficial action in pathological conditions.…”
Section: Discussionsupporting
confidence: 56%
“…These data are consistent with earlier findings (Upadhya et al, 2000, Hao et al, 2010) where CYP2E1 was found in GFAP + cells and, occasionally, in vessels. After severe status epilepticus (SE), CYP2E1 immunoreactivity was regionally increased in CA2/3 and hilar but not in CA1 hippocampal neurons (Figure 1A).…”
Section: Resultssupporting
confidence: 94%
“…The presented data and available evidences (Tindberg et al, 1996, Upadhya et al, 2001, Pardini et al, 2008, Hao et al, 2010, Mann et al, 2012, Zhong et al, 2012, Birnie et al, 2013) support the hypothesis of drug biotransformation in healthy and diseased brain ( e.g ., traumatic brain injury, ischemia, Alzheimer’s’ disease, epilepsy). Further studies are required to fully elucidate the functional relevance of selected P450 enzymes, such as CYP2E1, in the epileptic brain.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…CYP2E1 inhibitors protect the cell from damage and the production of ROS induced by 1-methyl-4-phenylpyridinium ions (MPP + ), LPS, and ethanol in wild-type primary astrocytes [82]. …”
Section: Protein Mrna and Activity Modulation Of Cyp2e1 In The Bmentioning
confidence: 99%